Food safety assessment of the mycotoxin and pesticide residue contamination of our foods, part 2. : Mycotoxins - Ambrus, Árpád; Szenczi-Cseh, Júlia; Griff, Tamás; Kerekes, Kata; Miklós, Gabriella; Vásárhelyi, Adrien; Szigeti, Tamás János (Élelmiszervizsgálati Közlemények, 2020)
The occurrence, legal regulation, quality requirements for sampling and analysis of mycotoxins occurring in food and feed in Hungary are presented. Furthermore, the current practice is evaluated. To complement the test results of NÉBIH, the WESSLING Hungary Ltd. and the University of Kaposvár provided detailed analytical results for the assessment of consumers’ exposure. Besides, the BIOMIN Ltd. and the SGS Hungária Ltd. shared their annual summary data, the Gabona Control Ltd. made available partial test results for preparing this paper. Based on the available data and information, the exposure of Hungarian consumers to Aflatoxin M1 and DON is estimated, and recom-mendations are made for facilitating the actions aiming to reduce the contamination of our food. Taking into account the extensive national test results and international information, we concluded that: • the exposure of consumers to Aflatoxin M1 and DON may exceed the toxicological reference values from time to time, posing a risk to consumers’ the health; • there is a need for coordinated comprehensive actions by all interested parties for the reduction of Aspergillus and Fusarium fungi infections in cereals and the resulted toxin exposure.